The Effect of High Intensity Interval Exercise on Changes in Basal Rate and Vo2max - Moh. Amrullah Albaitomi; Ali Maksum; Irmantara Subagio; Achmad Widodo (Budapest International Research and Critics University, 2022)
Football is an achievement sport that has special characteristics and physical characteristics for players. A good Vo2max endurance capacity can give an advantage to the athlete's performance when competing on the field. Football in Indonesia tends to have an average Vo2max which is still below the standard. One of the reasons is when adolescent athletes are never used to doing intensive physical exercise so that the training age is still small and it will take a long time to improve. In addition to increasing Vo2max, physical exercise also affects changes in suppressing the pulse. Because when someone with a low resting pulse rate, the endurance to carry out an activity, high-intensity exercise and competition will last longer. The purpose of this study is to find out and compare the effectiveness of the HIIT training method with two different forms or variants with a design according to the principle of load training on basal pulse and Vo2max. This study used a quasi-experimental design with Randomized Control Group Pretest-Posttest Design with a sample of 30 divided into 3 groups consisting of 10 athletes in the Shuttle run experimental group, 10 athletes in the around rectangle group and 10 athletes in the control group. Treatment is given within 8 weeks with 3 meetings per week using a Polar H10 device to control exercise intensity. Data analysis using (MANOVA) with the help of the SPSS statistical program. The results showed that the two exercises had a significant effect in improving the pulse p-value 0.001 < 0, 05 in the Shuttle run exercise and Vo2max 0.000 < 0.05, from Around rectangle on pulse p-value 0.000 < 0.05 and Vo2max 0.000 < 0.05. Meanwhile, the effectiveness of the two exercises is the same as the p-value 1,000 > 0.05. Therefore, HIIT is not based on its form but on its duration and intensity which is monitored using a heat rate check for each exercise.